Use and functioning of the castle ruins in Iłża - Drobek, Katarzyna; Trochonowicz, Maciej (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2021)
The article presents the current functioning, development, state of research and technical condition of the castle ruins in Iłża. The relics of the fortress are one of the most interesting objects located in the Masovian Voivodeship. Their location in the city shows great landscape values of the entire castle complex, which is the identification element of Iłża. For hundreds of years, the fortification has been kept in the form of a ruin and its form is preserved in the memory and consciousness of the society. The castle is currently open to tourist traffic. Archaeological research is also carried out there and new concepts for the development of the castle area are created.